Haze Disaster in South East Asia: An Urgent Study on the Effect of Dioxins to the Firefighters - Yin-Hui Leong; Ahmad Shalihin Mohd Samin; Mohamed Isa Abdul Majid (Annals of Environmental Science and Toxicology - Peertechz Publications, 2017)
Firefi ghters may be exposed to a wide variety of toxic chemicals in their line of work, including volatile organic compounds, polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), brominated fl ame retardants (BFRs), metals, and various combustion by-products [1-4]. Such exposures can occur through inhalation and skin contact, although advances in personal protection (e.g. clothing and breathing apparatus) have apparently reduced such risks in recent years. However, the major concern during fires is the potential formation of large amounts of harmful byproducts such as chlorinated and brominated dibenzo-pdioxins and dibenzofurans (PCDD/Fs and PBDD/Fs) [5,6] and polychlorinated biphenyls (PCBs) [7]. All of these contaminants belong to the persistent organic pollutants (POPs) and highly toxic substances that cause adverse effects on humans and ecosystem. Their toxic responses include immunotoxicity, carcinogenicity and several endocrine effects related to reproduction [8].